PERAN OPINION MINING DAN SENTIMENT ANALYSIS UNTUK MENGIDENTIFIKASIKAN SENTIMEN PUBLIK DALAM SISTEM E-GOVERNANCE (Universitas Palangka Raya, 2016)
People use text to communicate their emotion and opinion about some subjects.Currently government online media provides the facility for the citizen to express their opinions through text. E-governance system that built by the government will function better if the data that contains citizen's opinion not only saved but can be managed to be more valuable information.Opinion Mining and Sentiment Analysis is the science of natural language processing that could identify emotions, sentiments and main ideas expressed in the text. The government can take advantage by embedding the opinion mining and sentiment analysis methods in the e-governance system.Citizen's opinion about the services or policies of the government is an information that required by the Government in running the good government system. In this study, will be discussed some methods of opinion mining and sentiment analysis that have been performed by some previous researchs.